Say anything [videorecording (DVD)] - Crowe, Cameron, 1957-; Cusack, John, 1966-; Skye, Ione; Mahoney, John, 1940-2018 (Twentieth Century Fox Home Entertainment, 2002)
A young man, recently graduated from high school, wants only one thing: a date with a fellow graduate. The catch is she's beautiful, brilliant and headed to England to study, and all his friends and her father tell him she's way out of his league. When they fall in love anyway, the result is a funny, poignant and joyous celebration of first love.